Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1176/appi.ps.54.8.1142
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Participation and Problems Among South East Asian Refugees to the United States

Abstract: These data call for more research into the social, environmental, and cultural context of gambling among South East Asian refugees. Ethnically sensitive prevention and intervention strategies are needed to address the extraordinarily high rates of gambling problems in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
2
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 18 publications
1
51
2
6
Order By: Relevance
“…According to research conducted in Canada, the United States and Australia, South-east Asian refugees (Petry et al, 2003),Asians (Welte et al, 2001) and Chinese immigrants (Blaszczynski et al, 1998;Sin, 1996) show a higher rate of pathological gambling than the population average, which is estimated to be between 0.2% and 2.1% (Shaffer et al, 2004).The pre-disposition of Chinese immigrants to gambling and their higher prevalence of pathological gambling have been attributed to cultural values and practices, post-immigration stresses in acculturation and social isolation (Raylu & Oei, 2004;Sin, 1996;Tse et al, 2004;Wong & Tse, 2003). Since not everyone who gambles becomes a pathological gambler, understanding the pre-disposing, contributing and precipitating factors that put immigrants at risk of developing pathological gambling is important for informing culturallyappropriate prevention and treatment for Chinese immigrants (Tse et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to research conducted in Canada, the United States and Australia, South-east Asian refugees (Petry et al, 2003),Asians (Welte et al, 2001) and Chinese immigrants (Blaszczynski et al, 1998;Sin, 1996) show a higher rate of pathological gambling than the population average, which is estimated to be between 0.2% and 2.1% (Shaffer et al, 2004).The pre-disposition of Chinese immigrants to gambling and their higher prevalence of pathological gambling have been attributed to cultural values and practices, post-immigration stresses in acculturation and social isolation (Raylu & Oei, 2004;Sin, 1996;Tse et al, 2004;Wong & Tse, 2003). Since not everyone who gambles becomes a pathological gambler, understanding the pre-disposing, contributing and precipitating factors that put immigrants at risk of developing pathological gambling is important for informing culturallyappropriate prevention and treatment for Chinese immigrants (Tse et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…La diferencia de género también ha sido informada, siendo el sexo masculino más proclive a ludopatía e hipersexualidad; mientras que las mujeres tienen más probabilidad de desarrollar compras compulsivas (8,26) . En relación a factores sociales y culturales, se ha encontrado elevadas tasas de ludopatías en inmigrantes asiáticos (27) . Los datos existentes sugieren que grupos específicos de individuos con EP son particularmente susceptibles a desarrollar algún DCI durante el curso de la enfermedad, particularmente durante el tratamiento con un AD.…”
Section: Discussionunclassified
“…Internationally, anecdotal accounts, media reports and recent research studies have made reference to the increasing level of participation in gambling by people from Asian countries (Blaszczynski et al 1998; Chinese Family Life Services of Metro Toronto 1995; Cultural Partners Australia Consortium 2000; Petry et al 2003). For instance in Australia, it was found that members of the Chinese community were almost 50 percent more at risk of developing problem gambling compared with their Caucasian counterparts (Raylu & Oei, 2004).…”
mentioning
confidence: 99%
“…For instance in Australia, it was found that members of the Chinese community were almost 50 percent more at risk of developing problem gambling compared with their Caucasian counterparts (Raylu & Oei, 2004). Asian people from a refugee background (Marshall et al 2009;Petry et al 2003) and international students (e.g. Gambling Research Australia 2011) have been found to be particularly at risk of problem gambling.…”
mentioning
confidence: 99%